The Phenomenon of the Compassionate Science Ritual in the Javanese Community in Tembung Village, Percut Sei Tuan District - Muhammad Fadli; Ayu Febryani; Trisni Andayani; Fernando De Napoli Marpaung; Titin Rahmayanti Rambe (Universitas Medan Area, 2023)
The aim of this research is to describe the phenomenon of the ritual of compassion in the Javanese community in Tembung Village, Percut Sei Tuan District. The research method used is a qualitative method with an ethnographic approach that describes cultural phenomena and the location of the research was carried out in Tembung Village, Kec. Percut Sei Tuan. The data collection techniques used were observation, in-depth interviews with five practitioners of compassionate science and field documentation. The results of the research illustrate that the Science of Compassion has two types of ways to get it first by meditating while reciting the mantra which will be practiced secondly by fasting mutih, Monday-Thursday, and fasting the patih geni. Both of these methods are conditions that must be carried out by every practitioner who will practice them and the findings in the field show that there are two types of loving spells, namely loving spells that use Javanese and holy verses that have loving meanings which are also often used as a loving science which in general practitioners use Asmaul Husna recited a hundred times after praying. The conclusion is that the science of compassion is a spell that is taught to certain groups and is a cultural heritage that is believed to be able to help humans solve all the problems that society faces and this is also a cultural heritage that has been preserved by the Javanese people in Tembung Village.